Application of integrated models to assess the impacts of floodplain connectivity on ecosystem services: a case study at Tempsford, UK - Taktikos, Niko (Cranfield University, 2015)
Floodplains in the United Kingdom have evolved from natural landscapes to artificially modified ecosystems through managing lateral and vertical floodplain connectivity leading to synergy or trade-offs in ecosystem service delivery. Research methods have been limited in understanding the processes by which ecosystem service values are formed and the data required to support ecosystem service assessment. Developing a methodology while complex and challenging is necessary in order to take the ecosystem approach forward to support decision making for policy makers, planners and stakeholders. The aim of this research was to develop a method to assess the delivery of ecosystem services in response to changes in floodplain connectivity and evaluate the performance. A case study floodplain was selected at Tempsford, downstream of the River Ivel in Bedfordshire, United Kingdom as an example for opportunities to deliver multiple ecosystem services. A sequential integrated modelling system was applied utilising a linked ISIS 1D-2D hydrodynamic model and WaSim, a 1D soil water balance model to simulate changes in floodplain connectivity and generate model data to improve estimates of ecosystem services indicators. A non- monetary multi-criteria analysis methodology was applied to further develop indicators for ecosystem services assessment and to assess the impacts of the model scenarios on ecosystem services delivery. The integration of the WaSim model was unsuccessful as the model performed poorly in the calibration and validation process and was not fit for its intended purpose. It was deduced that potential groundwater seepage in the regional aquifer occurs outside of the field study site, which cannot be modelled in WaSim. To demonstrate the impact of lateral connectivity controls on the water table position, an empirical method was developed using the mean observed water table position to represent a ‘no drainage system’ vertical connectivity scenario. The results showed that in low frequency/high magnitude flood events, increasing the lateral connectivity by lowering embankments provides synergy and benefits to flood alleviation, water supply and freshwater fish habitat and trade-offs and disbenefits to flood damage, agricultural productivity, terrestrial habitat and recreation. In high frequency/low magnitude flood events, decreasing the lateral connectivity by raising embankments still provides the same synergy and trade-offs yet lower benefits and disbenefits. Marginally decreasing the lateral connectivity creates a higher level of benefits and a lower level of disbenefits to promote multi-functional land use in the floodplain. Managing the control of floodplain connectivity needs to be carefully planned to enable multifunctional land use in a floodplain.